Forest magic for kids : how to find fairies, make a secret fort, and cook up an elfin picnic - Spikol, Susie (Gibbs Smith, 2025)
Your enchanted guide to 50+ magical activities for everything from finding hidden flower fairies in your own backyard and making a special wizard staff to creating a tiny woodland village and making your own forest potions. Come discover the wild magic tucked into the nooks and crannies of forests, thickets, and meadows. Search for fairy dusted glow-in-the-dark mushrooms. Find secret worlds hidden in trees and uncover the tunnels, trails, and dens of gnomes and trolls, and mice and moles. Learn to listen to the forest, make sun-warmed pine tea, and wear an evergreen crown to an elf picnic.